EFFECT OF 2,4-DICLOROFENOKSIASETAT (2,4-D) AND BENZYL AMINOPURIN (BAP) ON THE GROWTH OF BINAHONG LEAF CENTER (ANREDERA CORDIFOLIA L.) AND ANALYSIS OF FLAVONOID TOTAL CONTENT - Lili Sugiyarto; Paramita Cahyaningrum Kuswandi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
The aim of this research was to study the effect of various concentration of Plant Growth Regulator in MS (Murashige and Skoog) media on callus growth of binahong leaf and total flavonoid content. The method used in the propagation of callus was the leaf explant of binahong with a Completely Randomized Design (CRD). The leaf explants were planted on MS media with different 2,4-D concentrations (1;2;3 ppm), 0,5ppm IBA+0,5ppm BAP; 0,5ppm IBA+1,0 ppm BAP ; 1,0 ppm IBA+0,5 ppm BAP, each with 15 repetition. The parameters observed in this research were initiation time, type, colour, diameter, the number of callus and total flavonoid content. The result showed that the optimum growth of callus is at 3 weeks and after that it declined or stayed stagnant. The result of the analysis of variance (ANOVA) showed that there is no significant difference in the media used in this research. The total flavonoid content of fresh leaf sample is higher than callus sample.